Health profile of workers from different industries in Singapore - Sin Eng Chia; Mei Ling Tan; Elise Cheok; Peh Woon Ong (Singapore Medical Journal)
Introduction: Workplace safety and health are interrelated — a worker who is not healthy may cause safety lapses at the workplace; conversely, safety lapses could affect the health of the workers. This study was part of a larger Total Workplace Safety and Health (WSH) programme run by the Workplace Safety and Health Council, Singapore. The objectives were to obtain a baseline health profile of workers across four major industries and identify important health risks for targeted workplace interventions. Methods: Five service providers (SPs) were appointed to run the Total WSH programme. As part of the programme, SPs conducted an anonymous basic health survey among workers of participating companies. Results: The responses of 6,373 respondents from the cleaning, construction, manufacturing, and transport and storage industries were studied. The overall response rate was 62%. Key health issues identified were high rates of obesity (22%) and smoking (24%) and low prevalence of regular exercise and healthy dietary habits. Chronic disease rates were similar to population self-reported rates (hypertension 15%, high lipid 12% and diabetes mellitus 6%). The workers reported high work stress (13%). Conclusion: Health issues are prevalent in the workforce and may affect work and employee safety. It is increasingly important for employees’ health to be considered in risk assessments and prioritised in workplace safety and health management systems and strategies. Health promotion interventions should be targeted, and multilevel and multicomponent initiatives should be integrated with pre-existing occupational safety programmes.